RESPONSIBILITY OF MICKEY HALLER IN THE LINCOLN LAWYER MOVIE - Safrudi, Imam (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
Abstract The aims of this research is to understand the responsibility of Mickey Haller as a lawyer. By using descriptive qualitative method, the writer will describes all things in the movie itself. The data were collected from some sources, such as books in library of Senayan ,Library of STIBA Nusa Mandiri,  Google books and Website. The writer found the result of analysis about an interesting character from Mickey Haller as main character. Mickey Haller is a lawyer with high responsibility in his work. It makes him never give up on solving the case at hand. Mickey Haller is known as a lawyer who can acquit his clients from criminal penalties although most of his clients are criminal such bikers, con artist, drunk drivers, and drug dealers. Besides Mickey Haller was responsible for the work, he is also responsible for the safety of his family. He protects his children and ex-wife of the evil people who do not like him. In this movie, Mickey Haller is also a person loyal to good friends and work together.  Keywords: Responsibility, main character, THE LINCLON LAWYER movie.